The Concept of Al-Ḥākimiyyah and its Divergence from the Concept of Sovereignty: An Analysis of Mawdūdī’s and Sayyid Quṭb’s Ideas - Obalowu, Issah Abeebllahi; Abdul Rahim, Adibah (University of Management and Technology, 2021)
The concept of al-ḥakimiyyah is a scholarly topic among different categories/discussed and debated by various types of researchers, globally. The term al-ḥakimiyyah was pronounced and brought into the Islamic and western dictionaries by Sayyid Abū ‘AlᾱMawdūdī and theoretically developed by Sayyid Quṭb. Sovereignty is the common and general word/term that is always used as the English word for/substitute for al-ḥakimiyyah. Thus, many researchers have analyzed al-ḥakimiyyahbased on the concept of sovereignty found in the western perspective, which has led to some misconceptions regarding the concept. So, this paper intends to address the concept of al-ḥakimiyyahin the discourse of Abu ‘AlᾱMawdūdī and Sayyid Quṭb and its divergence from the concept of sovereignty found in the western perspective. Qualitative approach was employed in this research to collect the data from different sources and analyze it accordingly in order to determine the areas of difference between both the concepts. The findings revealed the difference between these two concepts in terms of their literal and contextual meanings. Likewise, it was revealed that the concept of al-ḥakimiyyahhas some connotations which the western concept of sovereignty does not have. To summarize, the concept of sovereignty in the western perspective does not represent fully the concept of al-ḥakimiyyahas manifested by Sayyid Abū ‘AlᾱMawdūdī and Sayyid Quṭb